Reliability of safety performance indicator: compliance and effectiveness of safety programs in construction site - Shanmugam, Rames Kumar (2015)
Construction sector is one of the high risked industries among other industries with regard to its occupational safety and health concern. This study is composed of elements of safety programs and sub-element safety programs, the compliance of each safety program and its relative important index which determines the rank level of importance of each safety program through questionnaire thus ultimately reflect the reliability of safety performance indicator in the construction site. The study concludes Relative Importance Index for compliance of safety program in construction, it is notable from the RII Ranking table above that Comply Safety and Health Program Requirements rank the highest RII of 0.9588 in construction site to be Always Complied from the Subcontractor’s Management whereas the least compliance of safety program in construction site is ranked at last RII of 0.8294 to Update with New Information during Safety Task Briefing. Relative Importance Index for effectiveness of safety program in construction, it is notable from the RII Ranking table above that the most highest rank on the RII of 0.9294 indicates that it would be Very Effective if the Safety Committee Involvement in the Safety Inspection process in construction site whereas the last yet important ranking RII of 0.7647 in the effectiveness of safety program in construction site is the Frequency of The Safety Task Briefing in construction site.